Teacher Understanding of Pedagogy Competency in Tangerang - Azizah Husin (Bandar Lampung University (UBL), 2014)
Research purposes to determine teachers' understanding of the pedagogy competencies. Teacher's task is to implement educational and professional learning. Teachers are required to run the task in a professional manner. It is necessary for the mastery of professional education competencies. As a professional’s job, teachers are required to have competencies are applied in the educational process. One of the important competencies is pedagogy. Education and the learning process will more easily lead to the goals if teachers understand and apply the understanding pedagogy. The method of research is descriptive quantitative. Population was the elementary and secondary teachers. Total sample was 25 teachers SD. The techniques of research were total sampling. Data were analyzed by descriptive quantitative using percentages. The results showed overall understanding of the teacher competence of pedagogy in Tangerang, the score had not been satisfactory. It is suggested that enhanced teacher understanding pedagogy competencies.